Flame propagation and heat transfer characteristics of a hydrogen–air premixed flame in a constant volume vessel. (15th June 2016) - Yenerdag, Basmil; Minamoto, Yuki; Naka, Yoshitsugu; Shimura, Masayasu; Tanahashi, Mamoru
Abstract: Direct numerical simulation of a stoichiometric hydrogen–air turbulent premixed flame in a rectangular constant volume vessel has been conducted to gain fundamental insights into turbulence–flame interactions and heat loss characteristics under a pressure rising condition. The turbulent vortices are significantly weakened in the burnt side due to expansion and viscosity increase. The conditionally averaged turbulent kinetic energy is suppressed near the wall and it takes mostly constant in the rest of the domain which suggests that there is no significant turbulence production near the wall, and the wall just damps the turbulence in the present simulation's set up. It is found that the turbulent kinetic energy still takes a significant value in the burnt side due to the velocity induced by the expansion, not much inherent to the turbulent eddies. Temporal evolution of the wall heat loss characteristics is studied. Although the heat loss induced by the burnt gas dominates the total heat loss at the end of combustion, the heat loss induced by flame impingements contributes to substantial portion of total heat loss. Finally, turbulence–flame interactions modeling is studied using a conventional flamelet model for reaction rate closure. The result shows that turbulence–flame interaction mechanism does not change significantly under pressure rising conditions, suggesting that this model could be also used in a pressure-evolving combustion system without further modifications.